EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN PETA KONSEP PADA MATERI DIMENSI TIGA KELAS X SMA NEGERI 1 CAMPALAGIAN - Agus Salim Mardin (IAIN Ambon, 2016)
This study aims to determine whether there is a difference in students' mathematics learning outcomes that follow the model of cooperative learning with concept mapping approach with students who take cooperative learning model (without using concept maps). In addition, this study has the purpose to determine the effectiveness of cooperative learning model with the concept map approach to the material dimension of three classes X SMA Negeri 1 Campalagian. The results showed that: (1) There are differences in average mathematics learning outcomes (post-test) between students taught with cooperative learning model to approach the concept maps and students taught with cooperative learning model, it is shown by the results of the calculation of the t-test be the Sig = 0.001 at 5% significance level. (2) There are differences in average mathematics learning outcome (gain) between students taught with cooperative learning model to approach the concept maps and students taught with cooperative learning model, it is shown by the results of the t-test calculation of a value Sig = 0,000 at the 5% significance level. (3) The average score for math learning outcomes (post-test) Eksperimen1 class of 80.5588 with a standard deviation of 7.37 gain increased by 0.73 with a standard deviation of 0.079, while the average score of mathematics learning outcomes (post-test ) Eksperimen2 class of 74.1515 with a standard deviation of 7.35 increased gain of 0.65 with a standard deviation of 0.074. (4) The average score of student activity and class Eksperimen2 Eksperimen1 grade of 3.56 with the category of